PENGARUH PENGALAMAN KERJA DAN PERTIMBANGAN PROFESIONAL AUDITOR TERHADAP KUALITAS BAHAN BUKTI AUDIT (STUDI KASUS PADA KANTOR AKUNTAN PUBLIK DI MALANG) - Eka Saputri Nurmalasari; Anik Malikah; Junaidi Junaidi (Universitas Islam Malang, 2017)
This research is a research that analyze the factors that influence the quality of audit evidence. The purpose of this study is to obtain evidence of case studies on the relationship of work experience and auditors professional judgment on the quality of audit evidence. Populatioan in this study is the auditor who works at public accounting office in the city of Malang, while the sample of 50 auditors. The type of data used is multiple linear regression.The results of this study are the work experience and professional judgment of auditors have a significant influence on the quality of audit evidence.